Nivel de información y estrés familiar en la unidad de cuidados intensivos - Flores Amaya, Milagros Del Pilar (2015)
This study aimed to determine the level of patient status information and influence the level of family stress in the intensive care unit of Regional Hospital of Trujillo. January-June 2014. The methodology used was quantitative, not experimental, descriptive-correlational, prospective, transversal. The random sample consisted of 107 relatives of patients in September 2014. As the test instrument level information is used; for determining the level of stress the Perceived Stress Scale (Perceived Stress Scale, PSS) was used, both instruments met the reliability requirements. The chi-square test for related samples and contingency coefficient Pearson chi-square was used for statistical evaluation of association of variables. The results show: 1) The level of information to patients at Regional Hospital provided the relative of the intensive care unit is medium level (68%) and high (32%) this indicator information has the information delivery component that includes aspects such as empathy, assertiveness and nonverbal aspects. 2) The level of esters in the relatives of patients in the intensive care unit of teaching was half Regional Hospital (30%), high (14%) and very high (55%) and 3) demonstrated statistically that there is a relationship High-intensity reverse between the level of information and the level of stress (r = 0922, P = 0.000 <0.01) with a confidence level of 99%.